A Classroom Action Research in SMA Muhammadiyah 7 Makassar: The effect of Simulation Technique in Speaking Accuracy - Wongso Adi Saputra (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2017)
This research aimed to observe and know the improvement of students’ speaking skill at the second grade Exact students of SMA Muhammadiyah 7 Makassar which amount 22 students, that covers in accuracy and fluency through Simulation Technique in Classroom Action Research (CAR).To know the students’ improvement achievement, the researcher used Diagnostic test, test cycle II, and test cycle II. Before implementing test cycle I and cycle II, the researcher applied action to the students through two cycles, which covers four meetings for each cycle.Cycle I test result had showed the improvement in the students speaking skill in the comparison with the diagnostic test, that is 3.5 (3.4 for accuracy and 3.6 for fluency) in the diagnostic test but that improvement is still not complete the standard score which is 6.5, so that the researcher continued to apply cycle II. And in the test cycle II finally the students showed the improvement significantly which is 7 for accuracy. That result proved that Simulation Technique could improve the students’ speaking skill at the second grade exact students of SMA Muhammadiyah 7 Makassar.Heaton, J. B. 1975. Writing English Language Test. New York: Longman Inc.Heaton, J. B. 1988. Writing English Language Test. New York: Longman Inc.